The Importance Awarded to Human Resources and Human Resources Department in Companies from West Region of Romania - Nicolae BIBU; Anca-Ioana MUNTEANU (Revista de Management Comparat International)
In literature, works that have the theme of human resources are some widespread, long a subject being addressed. Given their irreplaceable role in any organization, certainly in the area will continue to be of interest to those in the field. This paper aims to conduct a research, which has two main goals: identifying the importance given to human resources in organizations in the West Region of the country, and whether the Human Resources Department acts as the strategic partner of top management. The study does not include all companies in the mentioned area, but only those large or very large (over 250 employees), regardless of the nature of capital (Romanian, foreign, mixed) or sector (public or private), but that are not subsidiaries of multinational companies, with independent position, being independent decision. The results obtained with this study confirms the change in terms of human resources and the role assigned to the Human Resources Department within organizations, namely those in the Western Region of Romania.